Assessments of Contamination and Susceptibility Pattern of Bacteria Isolated from Pounded Yam Sold Along Major Roads in Makurdi Metropolis, Benue State, Nigeria - Womboh, S. B.; Ajumobi, V. E.; Ebute, P. A. (UMYU Journal of Microbiology Research)
Pounded yam is a staple food consumed in Makurdi, Benue State. The food is sold along major streets and roads in the town, as such; it is prone to bacterial contamination from different sources. The study was aimed at assessing the contamination and susceptibility pattern of bacteria isolated from pounded yam sold along major roads in Makurdi metropolis. One hundred and forty (140) samples of pounded yam were aseptically collected from seven food vending sites (Wurukum, Wadata, High level, Naka road, Otukpo road, Gboko road and North bank) and analyzed for bacterial contamination using standard microbiological procedures. The Kirby-Bauer disk diffusion method was used for the antibacterial susceptibility testing. The antibiotics tested were Septrin, Chloramphenicol, Sparfloxacin, Ciprofloxacin, Amoxicillin, Augmentin, Gentamycin, Pefloxacin, Tarivid and Streptomycin. If a bacterial isolate proved resistant to at least three of the tested antibiotics, it was deemed to be multi-drug resistant (MDR). A total of four species of bacteria which included Staphylococcus aureus (35.66%), Escherichia coli (18.18%), Klebsiella spp (11.20%) and Proteus spp (34.97%), were isolated from the pounded yam samples. The mean total viable count of all the samples; which ranges from 2.61x105cfu/g (Wadata) to 3.25x105cfu/g (Otukpo road) are within the acceptable limits for food. Staphylococcus spp, Escherichia coli and Proteus spp were multidrug resistant to four, six and three antibiotics respectively, according to the antibacterial susceptibility test. Staphylococcus spp showed 31.37% susceptibility to Septrin, 37.25% to Streptomycin and 33.33% of the Staphylococcus isolates were sensitive to Sparfloxacin and Amoxycillin.  For Escherichia coli, more than 50% of the 26 Escherichia coli isolates showed resistance to Septrin (46.16%), Sparfloxacin (42.31%), Amoxicillin (42.31%), Gentamycin (38.46%), Perfloxacin ((46.15%) and Streptomycin (23.08%). Proteus spp showed 44.00% susceptibility to Chloramphenicol, 30.00% to Sparfloxacin and 40.00% to amoxicillin. Klebsiella spp showed 25.00% susceptibility to Amoxicillin only. The study identified that pounded yam sold along major roads in Makurdi metropolis are contaminated with bacteria of public health importance. Therefore hygienic way of food preparation is of utmost importance to prevent contamination of food with these organisms resulting to food borne diseases.